Cooperative design of broadband vibration energy recovery and thermal management for structural-exhaust systems in intelligent connected vehicles: A review - Wang, Chao (Sound & Vibration, 2026)
The rapid advancement of intelligent connected vehicles (ICVs) has placed new demands on distributed electronic systems and increased the number of on-board functions that involve sensing, communication, and control. Unlike conventional vehicles, ICVs have significantly higher energy demand, and real-time sensing, communication, and control capabilities are much more feasible and are key to enabling cooperative vibration-thermal design. Structural-exhaust systems are subjected to broadband vibrations and extreme temperatures at all times and therefore seem to be a good platform for waste energy recovery and thermal control. Vibration energy harvesting and exhaust thermal management have been widely studied, but they are mostly implemented individually as subsystems. This separation ignores the thermo-mechanical coupling in exhaust structures and typically results in inefficient energy recovery and poor thermal and/or structural performance. A thorough review of the cooperative design of broadband vibration energy recovery and thermal management for the structural-exhaust system of an ICV is presented. The vibration and thermal performance of exhaust systems, and the coupling mechanisms between them, are investigated to elucidate fundamental design issues. A review of state-of-the-art broadband vibration energy harvesting technologies and exhaust thermal management technologies is conducted, highlighting their limitations operating under coupled conditions. Cooperative design concepts, structural integration strategies and multi-physics modelling and optimization methods are explained. Adaptive control, vehicle-to-everything connectivity, data-driven techniques, digital twins and system-level validation are emphasized. Lastly, problems are identified, and areas for further research are suggested.